IMPLEMENTASI METODE TIME TOKEN BERBANTUAN MEDIA QUESTION BOX UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS ANEKDOT PADA SISWA KELAS X 1 SMA (SLUA) SARASWATI 1 DENPASAR TAHUN PELAJARAN 2024/2025 - Semuel, Hilda; Wedasuwari, Ida Ayu Made; Susrawan, I Nyoman Adi (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2025)
This research is a Class Action Research (PTK) which aims to (1) the implementation of the time token method with the help of Question Box media can improve anecdotal text writing skills in grade X 1 students of Saraswati 1 High School (SLUA) Saraswati 1 Denpasar. (2) to find out the steps of the time token method of Question Box media assistance in improving the ability to write anecdotal texts in grade X 1 students of SMA (SLUA) Saraswati 1 Denpasar. (3) to find out the response of students in class X 1 of SMA Saraswati 1 Denpasar after the implementation of the Time Token method with the help of Question Box media in an effort to improve the ability to write anecdotal texts. The data collection methods used are observation, tests, questionnaires and documentation. The data analysis methods are carried out in a qualitative descriptive and quantitative descriptive manner. The success indicator in this study is that if the writing ability of students is at least 75 with a good category, the steps to implement the time token method assisted by media question boxes show an increase in students reaching 80% and getting more respondents